2018
DOI: 10.1002/cmdc.201800434
|View full text |Cite
|
Sign up to set email alerts
|

Decoding the Rich Biological Properties of Noble Gases: How Well Can We Predict Noble Gas Binding to Diverse Proteins?

Abstract: The chemically inert noble gases display a surprisingly rich spectrum of useful biological properties. Relatively little is known about the molecular mechanisms behind these effects. It is clearly not feasible to conduct large numbers of pharmacological experiments on noble gases to identify activity. Computational studies of the binding of noble gases and proteins can address this paucity of information and provide insight into mechanisms of action. We used bespoke computational grid calculations to predict t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…Our previous validation study showed that in silico methods can accurately predict the binding sites of noble gases in proteins. Our methods recapitulated 399 experimental noble gases binding positions in 133 diverse proteins with accuracies between 97 and 100% . We found 94% of all the crystallographic xenon atoms were within 1 Xe van der Waals (VdW) diameter of a predicted binding site and 97% lay within 2 VdW diameters.…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations
“…Our previous validation study showed that in silico methods can accurately predict the binding sites of noble gases in proteins. Our methods recapitulated 399 experimental noble gases binding positions in 133 diverse proteins with accuracies between 97 and 100% . We found 94% of all the crystallographic xenon atoms were within 1 Xe van der Waals (VdW) diameter of a predicted binding site and 97% lay within 2 VdW diameters.…”
Section: Introductionmentioning
confidence: 82%
“…In these calculations, we assumed that removal of water and other solvents from the experimental structures would not affect the noble gas binding calculations. This is based on the results of the validation study where 399 experimental noble gas binding sites were correctly identified using the same assumption. Noble gases tend to be lipophilic and have low water solubility …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The accuracy of the numerical approach has been validated on existing crystallographic structures of proteins in complex with noble gases. 29 The results of a docking calculations consist of a potential binding energy for all locations around the protein based on a 0.3 Å computational grid. From these thousands of potential binding sites, the 20 most likely, based on their gas binding energy, have been selected for ranking.…”
Section: Introductionmentioning
confidence: 99%